Designing local policies and economic instruments to enhance waste management in Bayawan city, Philippines - Paul, Johannes G.; Boorsma, J.D.; Sarana, G.; Bollos, I. (2015)
To establish and operate reliable Solid Waste Management (SWM) systems, efficient technologies, stable organizational structures, skilled personnel, sound operational management and appropriate financing concepts are required. In order to sustain such systems, the implementation of suited legal framework conditions and economical instruments are considered as key success factors. Proper financial management allows to determine the real costs of SWM and to design local policies that provide the needed mechanisms to conduct Solid Waste Management on community level and to formulate rules and user fees that are not only acceptable by residents and users but likewise secure participation of stakeholders and transparency for the public [1, 3]. As in other developing countries, financing SWM remains a severe issue also in the Philippines. Cost recovery is an important requirement for sustainable waste management, but it does not always correspond with political priorities, the willingness of the population or the capacities of the administration to implement it. Fees to cover SWM costs are either not asked for, or existing fee mechanism are not effectively implemented or being utilized by the authorities in charge. However, policies that address cost recovery will directly affect the capacity and willingness of service recipients to pay as well as the maximum level of refinancing that can be achieved. The lower the level of cost recovery, the higher the resulting risk of poor services rendered or ultimately service interruptions. Hence, sustainable financing of SWM by local means is imperative. In Bayawan City, Philippines the local government recognized the opportunities arising with establishing a new SWM system as required by national waste legislation [5]. During SWM planning various issues surfaced that were taken up by the local authorities to design 'taylor-made' new local policies that integrate cost recovery mechanism through user fees and revenues for material recovery. Main positive effects of cost recovery resulted from introduction of a prepaid sticker system that requests to pre-pay a fee for collection of residual waste and bio-waste. Besides, the introduction of an environmental fee claimed with the regular water bill propelled cost recovery from initial 3% to more than 15% of annual SWM budget after only 3 years operation of the new system whereas income for the latter is mainly used for cleaning of septic tanks and processing of recovered sludge at the newly established municipal waste management center. Results of this case underline that enhancing SWM systems is possible also in developing countries with innovative technologies and approaches that integrate local conditions and provide suited mechanism to enhance motivation and ownership of local decision-makers and users likewise [2-4].